2018
DOI: 10.3390/catal8050218
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Persulfate Using an Industrial Iron-Rich Sludge as an Efficient Nanocatalyst for Landfill Leachate Treatment

Abstract: In this research, the performance of nanomaterials obtained from the converter sludge (CS) of Esfahan Steel Company, Iran was investigated for the activation of persulfate (PS). The experiments were conducted on real and synthetic leachates. CS showed high catalytic activity for removal of chemical oxygen demand COD and NH 3 because of its high iron oxide content. The effects of pH, CS dosage, and PS/COD ratio, temperature, and reaction time on the removal of COD and NH 3 were evaluated to optimize operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In a recent study [ 34 ], researchers investigated the treatment of landfill leachates using (industrial) iron activated persulfate. They found that when the initial chemical oxygen demand of the effluent decreased from 121 g/L to 18.5 g/L, the percentage removal increased from 17.2 to almost 48%.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study [ 34 ], researchers investigated the treatment of landfill leachates using (industrial) iron activated persulfate. They found that when the initial chemical oxygen demand of the effluent decreased from 121 g/L to 18.5 g/L, the percentage removal increased from 17.2 to almost 48%.…”
Section: Resultsmentioning
confidence: 99%
“…A Metrohm 691 pH meter was used to measure the pH of solutions. To quench the reaction, Soubh et al method was applied (43).…”
Section: Synthesis Of Rego-supported Nzvimentioning
confidence: 99%